Arbuscular mycorrhizal fungi are an alternative to the application of chemical fertilizer in the production of the medicinal and aromatic plant Coriandrum sativum L. Issue 7 (2nd April 2016) - Oliveira, Rui S.; Ma, Ying; Rocha, Inês; Carvalho, Maria F.; Vosátka, Miroslav; Freitas, Helena
ABSTRACT: The widespread use of agrochemicals is detrimental to the environment and may exert harmful effects on human health. The consumer demand for organic food plants has been increasing. There is thus a rising need for alternatives to agrochemicals that can foster sustainable plant production. The aim of this study was to evaluate the potential use of an arbuscular mycorrhizal (AM) fungus as an alternative to application of chemical fertilizer for improving growth performance of the medicinal and aromatic plant Coriandrum sativum . Plants were inoculated with the AM fungus Rhizophagus irregularis BEG163 and/or supplemented with a commercial chemical fertilizer (Plant Marvel, Nutriculture Bent Special) in agricultural soil. Plant growth, nutrition, and development of AM fungus were assessed. Plants inoculated with R. irregularis and those supplemented with chemical fertilizer displayed significantly improved growth performances when compared with controls. There were no significant differences in total fresh weight between plants inoculated with R. irregularis or those supplemented with chemical fertilizer. Leaf chlorophyll a + b (82%), shoot nitrogen (44%), phosphorus (254%), and potassium (27%) concentrations increased in plants inoculated with R. irregularis compared to controls. Application of chemical fertilizer inhibited root mycorrhizal colonization and the length of the extraradical mycelium of R. irregularis . Inoculation with R. irregularis was equally or more efficient than application of chemical fertilizer in promoting growth and nutrition of C. sativum . AM fungi may thus contribute to improve biologically based production of food plants and reduce the dependence on agrochemicals in agriculture.